(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
We describe the anaesthetic management of 2 years old Craniopagus twins for cerebral angiogram &embolization. Anesthetic management for Craniopagus twins is associated with unique concerns of crosscirculation, difficulty in mask ventilation, difficult access to airway and intubation due to angle betweenthe heads.Adequate preparation and teamwork is the keystone to the management of these patients. JBSA 2019; 32(1): 35-37